2022
DOI: 10.1002/jsfa.12369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sous vide cooking combined with ultrasound pretreatment on physicochemical properties and microbial communities of Russian sturgeon meat (Acipenser gueldenstaedti)

Abstract: BACKGROUND The production of Russian sturgeon is expanding rapidly in China but it is necessary to adopt measures to extend the shelf life of sturgeon meat. Previous studies found that sous vide cooking (SVC) at 60 °C increased the protein and lipid oxidation. The addition of antioxidant substances reduced the acceptance of the product. The effect of combination SVC and ultrasound pretreatment was therefore investigated. RESULTS Results showed that SVC at 50 °C combined with ultrasound effectively restrained t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Previous research indicated that the enzymatic hydrolysis of lipids was significantly promoted by increases in water activity in food models [42]. A similar reduction in lipoxygenase activity in fresh Russian sturgeon (Acipenser gueldenstaedti) steak was observed during chilled storage at 4 °C [43]. In contrast, the lipoxygenase activity of grass carp (Ctenopharyngodon idella) that was pre-treated with 0.3% chlorogenic acid showed notable increases during short-term preservation at 4 °C, and then showed a downward trend after 8 days [44].…”
Section: Neutral Lipase Alkaline Lipase and Lipoxygenase Activity Ana...supporting
confidence: 52%
“…Previous research indicated that the enzymatic hydrolysis of lipids was significantly promoted by increases in water activity in food models [42]. A similar reduction in lipoxygenase activity in fresh Russian sturgeon (Acipenser gueldenstaedti) steak was observed during chilled storage at 4 °C [43]. In contrast, the lipoxygenase activity of grass carp (Ctenopharyngodon idella) that was pre-treated with 0.3% chlorogenic acid showed notable increases during short-term preservation at 4 °C, and then showed a downward trend after 8 days [44].…”
Section: Neutral Lipase Alkaline Lipase and Lipoxygenase Activity Ana...supporting
confidence: 52%
“…It is also stated that the compounds detected by TBARS analysis are very reactive and the TBARS value may be determined lower since the compounds they form by interacting with different compounds such as amino acids and proteins in meat are not determined as a result of the analysis (Özyürek, 2021). Yuan et al (2023) found that the TBARS values of Russian sturgeon meat cooked with the sous vide technique increased depending on storage. Karki et al (2023) stated that the TBARS values of tilapia fish cooked with the sous vide technique were within acceptable consumption limits until the end of storage.…”
Section: Ph Tbars and Tvb-nmentioning
confidence: 98%